IS WORDWALL EFFECTIVE IN TEACHING ENGLISH TO ELEMENTARY SCHOOL STUDENTS OR NOT? - Mahaputri, Dwi Settya; Jon Nizar (ELP (Journal of English Language Pedagogy), 2025)
This study aims to analyze the effect of the use of Wordwall media on English language learning in elementary school. This research is experimental research. The study was conducted at SDN 04 Bukik Sikumpa, Lareh Sago Halaban District, Lima Puluh Kota Regency, involving two groups of students: an experimental group using Wordwall media and a control group using conventional methods. The results showed that the average value of the experimental group was 77, while the average value of the control group was 65. T-test analysis produced a t_hitung value of 6.078, which is higher than the t_tabelvalue of 2.021. This shows that there is a significant influence of the use of Wordwall media on English learning. Thus, the hypothesis proposed, namely the presence of the influence of Wordwall media in the teaching of English to elementary school students, is acceptable. This research makes an important contribution to the development of more effective methods of teaching English at the primary level.